Brewery Effluent Treatment with Conventional and Natural Coagulants - Ramesh Babu Aremanda; Filmon Berhane; Heaven Daniel; Abiel Mehari; Arsiema Tekle (Program studi Teknik Kimia UNS, 2022)
ABSTRACT. In water scarce countries such as Eritrea, maintaining brewery industry remain ever challenging task. Currently, Asmara breweries is the only beer producing factory consuming 8.46 L of water per every L of beer produced which is notably higher than Brewer’s Association (BA) benchmark and consequently generates 7.53 L of wastewater/L of beer. Bottle cleaning and brewery activities ascertain ample effluent bases. Wastewater from bottle cleaning (BCWW), brewery (BWW) and mixed (MWW) have attributed a wide spectrum of 3500-160000 mg/L of COD and 327-26667 mg/L of BOD5, which are significantly overtops other reported brewery effluents. Physicochemical treatments including coagulation with conventional (alum) and natural (MO seed) flocculants have tested to remove higher COD and BOD5 concentrations of brewery effluents. Optimal coagulant dosage determined by accounting turbidity as a key performance indicator. Alum treatment of BCWW and MO seed flocculation of MWW have resulted in lower turbidity levels of 0.49 and 6.17 NTU at 60 mg/L of dosages respectively. The optimal quantities of 92.2 % and 86.6% (by weight) of water recovered from alum treatment of BCWW and MO seed coagulation of MWW respectively. Higher sludge volumes recorded as a major disadvantage in alum coagulation whereas natural coagulant, MO seed manifested competitive results in removal of COD, BOD5, Chlorine, Nitrogen, Sulphate, Sodium, TDS and TSS along with PH stabilization. In addition, 97.2% of influent turbidity removed through MO seed coagulation treatment, an equipollent to alum despite of four fold increment in potassium levels.Keywords: Brewery Wastewater Coagulation Alum Moringa Oliefera Effluent Treatment